Knowledge translation: translating research into policy and practice - Nelly Donszelmann Oelke; Maria Alice Dias da Silva Lima; Aline Marques Acosta
Objective: This paper provides a theoretical-reflective study of knowledge translation concepts and their implementation processes for using research evidence in policy and practice.Results: The process of translating research into practice is iterative and dynamic, with fluid boundaries between knowledge creation and action development. Knowledge translation focuses on co-creating knowledge with stakeholders and sharing that knowledge to ensure uptake of relevant research to facilitate informed decisions and changes in policy, practice, and health services delivery. In Brazil, many challenges exist in implementing knowledge translation: lack of awareness, lack of partnerships between researchers and knowledge-users, and low research budgets.Conclusions: An emphasis on knowledge translation has the potential to positively impact health outcomes. Future research in Brazil is needed to study approaches to improve the uptake of research results in the Brazilian context.